Factors Associated with Anemia Among Pregnant Women in Indonesia: A Multivariable Analysis of the 2023 Indonesian Health Survey - KHOTIMAH, HUSNUL; Jubaedi, Ahmad; Sakinah, Innama (Journal of Religion and Public Health, 2026)
Maternal anemia remains an important public health problem in Indonesia despite national iron-folic acidsupplementation and antenatal care programs. Updated national evidence is needed to identify groups requiring more targeted prevention. This study examined factors associated with anemia among pregnant women in Indonesia using the 2023 Indonesian Health Survey. This was a cross-sectional analysis of secondary data from SKI 2023. The analysis included pregnant women with hemoglobin measurement and complete covariate information. The weighted analytical population represented 121,339 pregnant women; the exact unweighted analytic sample should be reported from the final cleaned dataset. Anemia was defined as hemoglobin <11 g/dL. Survey weights, strata, and primary sampling units/clusters were incorporated in the analysis. Weighted descriptive statistics, design-adjusted Rao-Scott chi-square tests, and survey-weighted multivariable logistic regression were used. Adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were reported. The weighted prevalence of anemia was 28.2%. In the adjusted model, anemia was associated with age at risk (<20 or >35 years) (AOR=1.69; CI: 1.63-1.74), being unemployed (AOR=2.46; CI: 2.38-2.55), irregular ANC visits (AOR=1.41; CI: 1.36-1.47), chronic energy deficiency (AOR=1.28; CI: 1.24-1.33), and non-adherence to iron folic acid supplementation (AOR=1.44; CI: 1.40-1.48). Low maternal education (AOR=0.82; CI: 0.80-0.84) and incomplete ANC quality (AOR=0.34; CI: 0.32-0.36) showed inverse associations that require cautious interpretation because they may reflect coding/reference-category issues, detection bias, gestational-age-related measurement, or residual confounding. Strengthening design-based monitoring, targeted ANC counseling, and community-supported adherence strategies may help reduce anemia among pregnant women, particularly among economically vulnerable groups. Keywords: antenatal care; chronic energy deficiency; iron supplementation; maternal anemia; maternaloccupation